\[x_i, 1 \leq i \leq n\] \[y_i = a \times x_i + b\]

Se \(a=0\)

\[y_i = 0 \times x_i + b = b\] Se \(a=1\) e \(b=0\)

\[y_i = 1 \times x_i + 0 = x_i + 0 = x_i\]

Primeiro, aplicando a definição da média temos:

\[\text{Média}(y_i) = \bar{y} = \frac{\sum_{i=1}^n y_i}{n} = \frac{y_1+y_2+...+y_n}{n} = \]

Substituindo \(y_i\) pela relação \(y_i = ax_i+b\) teremos:

\[\frac{(ax_1+b) + (ax_2+b) + ... + (ax_n+b)}{n} = \frac{nb + ax_1+ax_2+...+ax_n}{n} = \] \[\frac{nb}{n}+\frac{ax_1+ax_2+...+ax_n}{n} = b + \frac{ax_1+ax_2+...+ax_n}{n} = \]

\[b + \frac{ax_1+ax_2+ax_3+ax_4+...+ax_n}{n} = b + \frac{a(x_1+x_2)+ax_3+ax_4+...+ax_n}{n} = \]

\[b+\frac{a(x_1+x_2+x_3+x_4+...+x_n)}{n} = b + a \times \left(\frac{x_1+x_2+...+x_n}{n}\right) = \]

\[b+a \bar{x}.\]

Logo, juntando os passos acima mostramos que:

\[Média(aX+b) = a Média(X)+b\]